Analysis of Antioxidant and Prebiotic Properties of selected seed extracts for Potential Nutraceutical Applications (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research evaluates the antioxidant and prebiotic potentials of the seed extracts obtained from Cucumis melo (musk melon), Punica granatum (pomegranate) and Linum usitatissimum (flax seeds) with a view of establishing nutraceutical functionality. Some of the merit making activities included preparation and characterization of the seed powders, physical characteristics, proximate composition and determination of antioxidant activity using DPPH assay. Furthermore, the ability of seed extracts to support the growth of beneficial bacterial strain was checked using Lactobacillus Acidophilus ATCC 4356 and Bifidobacterium bifidum ATTC 29521. The outcomes suggested that the seed powders’ combination held higher antioxidant activity than the seed powders alone and had substantial prebiotic functionality even superior to that of chicory powder well-known as a prebiotic. Based on the findings of this study, the seed extracts have immense potential to be used in the formulation of functional food-utritional supplements with antioxidant and prebiotic characteristics.